Ecological Integrity, Law and Governance
1 online resource
Keywords: "Ecological integrity is concerned with protecting the planet ina holistic way, while respecting ethics and human rights. Over recent years it has been introduced directly and indirectly in several legal regimes, culminating in international law with the 2016 expanded remit of the International Criminal Court,which now includes "environmental disasters". This book celebrates the 25th anniversary of the Global Ecological Integrity Group (GEIG), which includes more than 250 scholars and independent researchers worldwide, from diverse disciplines, including ecology, biology, philosophy, epidemiology, public health, ecological economics, and international law. It reviews the role of ecological integrity across a number of fields through inter- and trans-disciplinary engagement on matters affecting and governing the sustainability of life for both present and future generations. These include, ethics, environmental disasters, crimes against humanity and environmental health, and how such issues can be subject to sound governance and be incorporated into international law. The book also looks forward to new applications of the concept of ecological integrity, such as crimes that result in the exploitation of natural resources and the illegal dispossession? of land."--Provided by publisher.